An introduction to Vedanta - Jnanananda Bharati, Swami, 1889- (Sri Jnanananda Grantha Prakasana Samithi, 1976)
Summary of lectures delivered -- in the Sri Sringeri Sankara Mutt at Hyderabad and published in the Vedanta kesari of Madras.